STRATEGI PEMERINTAH KOTA PADANG DALAM PENGEMBANGAN PARIWISATA BERBASIS MITIGASI BENCANA - Erien Sri Wahyuni; Roni Ekha Putera; Yoserizal Yoserizal (Jurnal Pendidikan Ilmu Sosial, 2020)
This research in the background with Padang City is one of the cities that has existing tourism potential, where Padang City itself has vulnerability and vulnerability to disasters on existing tourist objects. This is a concern or concern for the city government of Padang if you want to develop tourism. On the one hand, Padang City has strong tourism potential, and on the other hand, Padang also has a high vulnerability to disasters. Thus, of course, the Padang City Government needs to create or manage tourism development strategies in disaster-prone areas. This study uses the theory of types of a plan initiated by Kotten. In this theory, there are four types of policies, namely: Organizational Strategy, Program Strategy, Resource Support Strategy, Institutional Strategy. The method used in this study is qualitative with a descriptive approach, data collection techniques used are interviews and documentation, while the method for selecting information is using a purposive sampling technique. To test the validity of the data obtained in the field, researchers used source triangulation. Based on the findings in the area, the Padang City Government has a strategy to develop tourism based on disaster mitigation, which through the Department of Tourism and Culture and the Padang City Regional Disaster Management Agency, has programs related to the development of disaster-based tourism mitigation.